(untitled) (RIAF. International Journal of Physical Activity, 2024)
Shoulder techniques in judo are the most commonly applied by athletes, regardless of age, gender, category, and weight. These techniques are of great importance in Go Kyu (the beginner level), and from the beginning of training, they are techniques that are learned, refined, and perfected throughout an athlete’s career. Their preparation must be methodologically guided. Therefore, a set of physical and technical exercises was proposed to achieve better performance of Kata waza (shoulder techniques) in athletes from the children’s category of the Guayas Sports Federation through its provincial Judo Association. The objective was to develop an appropriate methodology, using technical and physical exercises, for the teaching, development, and training of shoulder techniques, applying a research work where quantitative experimental methods are used and refined through the statistical analysis of primary and bibliographic data. The research is descriptive and experimental, using a mixed qualitative and quantitative approach to identify the characteristic problems of shoulder techniques. The population consisted of 24 athletes, 14 at the Juan Carlos Faidutti Dojo and 10 at the Huancavilca Sports Complex Dojo. The sampling was intentional, aiming to control the progress of the 14 athletes. Ultimately, there was a significant impact on sports performance, physical and technical abilities, as represented by the first tests. There was also improvement in mood and social aspects, as the athletes felt motivated to work on each training session with the basic principle of improving both individually and collectively, feeling stronger, faster, and more resistant to stimuli with each sports session.